A Kinetic Investigation of Regioselective Solvation of a Solvatochromic Dye in Aqueous Alcohols - Caroli-Rezende, M; Dominguez-Caru, M (John Wiley and Sons Inc., 2015)
The kinetics of methylation of the solvatochromic dye 4-[(2,4-dinitrobenzyli-dene)imino]-2,6-diphenylphenolate by dimethyl sulfate was investigated in three aqueous alcohols (1-propanol, ethanol, and methanol), in the search of a sharp change in its reactivity in water-rich media. The observed kinetic results paralleled previous observations of a sharp change in the solvatochromic behavior of the dye in the same media and was supported by a QM/MM simulation of the dye in two methanol-water mixtures, which rationalized the observed sharp change in the phenolate reactivity. © 2015 Wiley Periodicals, Inc.